PERBANDINGAN PENGATURAN PENYELENGGARAN PENDIDIKAN PROFESI ADVOKAT (PPA) DI INDONESIA DAN AMERIKA SERIKAT - Arif Setiawan; Lucky Suryo Wicaksono; Siti Anisah; Eko Rial Nugroho (Arena Hukum, 2017)
AbstractThis research is intended to examine the organization of advocate professional education in Indonesia and United States as well as how the organization of advocate professional education should be applied in Indonesia. This research was conducted by normative method that analyzes the data with referring to the legal norms contained in legislation and judicial decisions as well as using a comparative approach (comparative law) to United States. The results show that the First, there are differences in the organization of Advocate Education in Indonesia and United States. Organization of advocate professional education in the United States conducted by the law school while in Indonesia carried out by the Advocates organization. Secondly, Advocates professional education in Indonesia should not be in the form of Special Education Advocate Profession (PKPA). Special Education Advocate Profession actually is a form of professional education. Professional Education as part of a higher education course should meet national standards of higher education.Â AbstrakAdvokat merupakan salah satu profesi hukum yang memiliki peran penting dalam system peradilan pidana Indonesia. Tulisan ini bertujuan untuk mengkaji pengaturan penyelenggaraan pendidikan profesi advokat di Indonesia dan Amerika Serikat serta bagaimana penyelenggaraan pendidikan profesi advokat yang seharusnya diterapkan di Indonesia. Tulisan ini merupakan hasil dari satu penelitian yang menggunakan metode penelitian hukum normatif dengan menggunakan menggunakan pendekatan perbandingan hukum (comparative law) terhadap Amerika Serikat. Â Hasil penelitian tersebut menunjukan bahwa penyelenggaraan Pendidikan Profesi Advokat di Amerika dilakukan oleh sekolah hukum sedangkan di Indonesia dilakukan oleh organisasi Advokat. Pendidikan profesi Advokat di Indonesia seharusnya bukan dalam bentuk Pendidikan Khusus Profesi Advokat. Pendidikan Profesi Advokat sejatinya merupakan bentuk pendidikan profesi. Pendidikan Profesi Advokat sebagai bagian dari pendidikan tinggi tentunya harus memunuhi standar nasional pendidikan tinggi.